Antioxidant Potential Overviews of Secondary Metabolites (Polyphenols) in Fruits. (7th May 2020) - Swallah, Mohammed Sharif; Sun, He; Affoh, Raïfatou; Fu, Hongling; Yu, Hansong
Abstract : The rise in consumption of energy-dense foods has resulted in the displacement of several essential dietary gaps, causing numerous long-lasting diseases, including obesity, stroke, hypertension, and several forms of cancer. Epidemiological studies encourage more fruit consumption to prevent these diseases. The defensive mechanisms provided by these fruits against illness are due to the existence of several antioxidants. Recent studies proved that (poly) phenolic compounds are ideally the core phytochemicals with both functional and health-promoting properties found in the plant's kingdom, and low intake could result in the risk of certain diseases. Phytonutrients are powerful antioxidants that can modify metabolic activation and detoxification of carcinogens. The ideal motive of this review is to provide an overview as well as illuminate the polyphenolic merits of fruits in general. Fruits have several merits, including weight maintenance, proper health development, and satiety. There are many analytical methods for determining and measuring the phenolic content of different products. Phenolic compounds are of nutritional interest since they aid in the retardation and inhibition of lipids by acting as scavengers that prevent and protect the proliferation of oxidative chains. Future studies are required to help identify the physiological metabolic activities as well as to improve human health.